PERCEPTION AND MOTIVATION OF STUDENTS ON EFL LEARNING THROUGH PODCASTS - Aisyah Sahla Saudah; Tiara; Rizqi Ilham; Naf’an Tarihoran (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2026)
Podcasts have grown into one of the most effective digital media for supporting English language learning among EFL students. This study examines students' perceptions and motivation toward podcast use at UIN Sultan Maulana Hasanuddin Banten, Indonesia, exploring both constructs within a single quantitative framework, an approach that has received limited attention in Indonesian higher education. A quantitative descriptive design was employed, involving 90 students from semesters 2, 4, and 6 of the English Language Education Department. Data were gathered through a 20-item closed-ended questionnaire with a four-point Likert scale via Google Forms and analyzed using mean, standard deviation, and response percentages. Results indicate that students demonstrated largely positive perceptions of podcasts, with mean scores ranging from 2.93 to 3.31, especially regarding accessibility, pronunciation, and vocabulary development. Motivation was equally encouraging, with mean scores ranging from 2.87 to 3.26, reflecting persistence and eagerness to improve English proficiency. Nevertheless, difficulties in comprehending content and managing independent study time were noted. The study affirms that favorable perceptions correlate with stronger intrinsic motivation, providing valuable insights for lecturers, students, and institutions aiming to incorporate podcasts into EFL instruction more effectively.